Mixed matrix hollow fibre membrane comprising polyetherimide and modified montmorillonite with improved filler dispersion and CO2/CH4 separation performance - Jamil, A. (Elsevier Ltd, 2017)
Mixed matrix membrane with nano-filler embedded in polymer matrix, is receiving overwhelming attention for gas separation applications due to its attractiveness in providing an economic solution to enhance permselectivity. However, achieving uniform dispersion of nano-filler in host polymer remains a key challenge in developing membrane. In this work, mixed matrix hollow fibre membranes comprising polyetherimide (PEI) with various modified montmorillonite (f-Mt) loading, was developed via phase inversion method for CO2/CH4 separation. The Mt was modified with aminolauric acid to impart organophilicity to enhance compatibility towards organic polymer matrix. The synthesized hollow fibers were characterized using field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX), thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), and permeation test. The permeation tests were carried out with pure gases at ambient temperature with varying pressures of 2 and 4 bars. An increasing trend in ideal selectivity was observed up to 2 wt f-Mt loading. Thereafter, opposite trend was observed with increasing filler loading due to exfoliated layers that created more tortuous path for the penetrating gas molecules. The maximum ideal selectivity was found with 2 wt f-Mt loading at 2 bar, which showed 39 increment as compared to neat PEI hollow fibre membrane. This increment in gas selectivity was related to the dispersion state and aspect ratio of f-Mt. Various phenomenological models were employed to calculate the aforementioned properties. Adopting to Cussler and Yang-Cussler models, the aspect ratio of the f-Mt was found to be 35 and 50, respectively with 3–4 particles per tactoid. © 2017 Elsevier B.V.